Prevalence and Pathology of Helminth Infections in Pigs (Biological Sciences - PJSIR, 2008)
. In 30 viscera of local slaughtered pigs from different areas of Tangail and Mymensingh districts of Bangladesh, six species of helminths were identified; 2 of them were trematodes namely Fasciolopsis buski (36.70%) and Gastro- discoides hominis (26.70%) and 4 species were nematodes namely Ascaris suum (60%), Metastrongylus elongatus (53.33%), Stephanurus dentatus (10%) and Physocephalus sexalatus (56.71%). Three nematode species, viz. M. elongatus extracted from lung, S. dentatus from peri-renal fat and P. sexalatus from stomach, were recorded for the first time in pigs in Bangladesh. No gross lesion was observed in pigs affected with M. elongatus. In A. suum infection, intestinal wall was infiltrated with plasma cells, lymphocytes and eosinophils. In M. elongatus infection, lymphocytes and macrophages mainly eosinophilic infiltration was observed in the parenchyma of lung. Age exerted a significant (p